Refining Land Dispute Resolution in Indonesia’s Judicial System: An Economic Analysis of Legal Integration - Tambunan, Rico J.R.; Safa`At, Rachmad; Permadi, Iwan; Sulistyarini, Rachmi (Nurani Hukum, 2025)
Land dispute resolution in Indonesia is complex, involving multiple legal, social, and economic factors. Current mechanisms, including civil, administrative courts, and alternative methods like mediation, often fail to provide efficient or reliable outcomes, leading to legal uncertainty. This research examines the integration of dispute resolution mechanisms into Indonesia's judicial system from an economic analysis of law perspective. By applying principles of economic efficiency, the study explores how integration can reduce transaction costs and accelerate resolution processes. Using qualitative methods, the research analyzes legal documents, regulations, and court decisions to identify systemic challenges and propose improvements. The findings suggest that incorporating economic efficiency into the judicial process could enhance legal clarity, overcome existing obstacles, and restore public trust in land dispute resolution. This study contributes to the ongoing reform of Indonesia's legal system, offering insights into more effective, cost-efficient approaches to dispute resolution